Case Report: A novel RRM2B variant in a Chinese infant with mitochondrial DNA depletion syndrome and collective analyses of RRM2B variants for disease etiology - Wang, Yanjun; Hang, Ling; Shou, Weihua; Li, Cuifen; Dong, Fangling; Feng, Xingxing; Jin, Ruohong; Li, Bin; Xiao, Shufang (Frontiers in Pediatrics, 2024)
Background There are few reports of infantile mitochondrial DNA depletion syndrome (MDDS) caused by variants in RRM2B and the correlation between genotype and phenotype has rarely been analyzed in detail. This study investigated an infantile patient with MDDS, from clinical characteristics to genetic causes. Methods Routine physical examinations, laboratory assays, which included gas chromatography-mass spectrometry of blood and urine, and MRI scans were performed to obtain an exact diagnosis. Whole-exome sequencing was used to pinpoint the abnormal gene and bioinformatic analyses were performed on the identified variant.The case presented with progressive neurologic deterioration, failure to thrive, respiratory distress and lactic acidosis. Sequencing revealed that the patient had a homozygous novel missense variant, c.155T > C (p.Ile52Thr), in exon 2 of the RRM2B gene. Multiple lines of bioinformatic evidence suggested that this was a likely detrimental variant. In addition, reported RRM2B variants were compiled from the relevant literature to analyze disease etiology. We found a distinctive distribution of genotypes across disease manifestations of different severity. Pathogenic alleles of RRM2B were significantly enriched in MDDS cases.The novel variant is a likely genetic cause of MDDS. It expands our understanding of the pathogenic variant spectrum and the contribution of the RRM2B gene to the disease spectrum of MDDS.